Niceto Alcalá-Zamora : vida íntima y política de un jefe de estado / Eduardo M. del Portillo, Carlos Primelles - Primelles, Carlos; Portillo, Eduardo M. del
Edición facsímil de la ed. : Madrid : Biblioteca Nueva, 1932